2013
DOI: 10.1186/1472-6963-13-386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of comprehensive intervention on health-related quality of life in patients with chronic hepatitis B in China

Abstract: BackgroundHepatitis B virus (HBV) infection is a significant global health problem, especially in China. Chronic liver disease affects health related quality of life (HRQOL). The intervention method to improve HRQOL in patients with hepatitis B has been one-dimensional with inconsistent results. The purpose of this study was to evaluate the effect of comprehensive intervention on health-related quality of life and provide guidance on improving HRQOL for patients with chronic hepatitis B.MethodsPatients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
2
15
0
6
Order By: Relevance
“…As Taylor et al (15) also noted, the use of face-to-face social support and connection with trained healthcare providers may be vital to overall QOL and GFD compliance. From this and other research (15,19,20) , it appears that practice recommendations for individuals with CD should include referrals to a coeliac support group and a coeliac specialist dietitian, as well as planned continued care and monitoring.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
See 2 more Smart Citations
“…As Taylor et al (15) also noted, the use of face-to-face social support and connection with trained healthcare providers may be vital to overall QOL and GFD compliance. From this and other research (15,19,20) , it appears that practice recommendations for individuals with CD should include referrals to a coeliac support group and a coeliac specialist dietitian, as well as planned continued care and monitoring.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…Several studies have shown a positive association of face‐to‐face support groups on QOL in individuals with various medical conditions, albeit none on CD. There have also been multiple studies on the use and efficacy of face‐to‐face support group participation in the treatment and survivorship of various types of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in some countries, monitoring HRQOL in chronic hepatitis C patients has become a standard procedure [4]. Similarly, the awareness of the importance of HRQOL assessment in CHB has increased [5–12]. Unfortunately, based on the results obtained from a healthy population, some results point to a decrease in quality of life in CHB patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…CHB can result in a wide spectrum of liver diseases, including CHB, cirrhosis and hepatocellular carcinoma (1). Although HBV is noncytopathic, it is generally accepted that the outcome of HBV infection is mediated by the host immune response to HBV rather than the virus itself (2).…”
Section: Introductionmentioning
confidence: 99%